Function verification of a chlorophyll a/b binding protein gene through a newly established tobacco rattle virus-induced gene silencing system in Kandelia obovata - Zhang, Mingxiong; Rao, Yuhui; Chen, Xiaofeng; Shi, Yunrui; Wei, Chonglong; Wang, Xianfeng; Wang, Lu; Xie, Chengjin; Pan, Chenglang; Chen, Jianming (Frontiers in Plant Science, 2023)
As an important mangrove species, Kandelia obovata plays an irreplaceable role in the coastal ecosystem. However, due to a lack of genetic technology, there is limited research on its functional genes. As such, establishing an efficient and rapid functional verification system is particularly important. In this study, tobacco rattle virus (TRV) and the phytoene desaturase gene KoPDS were used as the vector and target gene, respectively, to establish a virus-induced gene silencing system (VIGS) in K. obovata. Through optimizing the pH of the resuspension buffer and the concentration of Agrobacterium for infection, the highest PDS gene-silencing efficiency could reach 92% after 10 days of inoculation and maintain above 80% after 15 days, which was achieved with resuspension buffer at pH 5.8 and Agrobacterium culture at OD600 of 0.4-0.6. Besides, the system was successfully used to verify the role of a Chlorophyll a/b binding protein (Cab) gene KoCAB in leaf carbon sequestration of K. obovata in combination with comparative transcriptome analysis. Taken together, the TRV-mediated VIGS system established herein is the first genetic analysis tool for mangroves, which may greatly impel functional genomics studies in mangrove plants.